2019
DOI: 10.3310/phr07150
|View full text |Cite
|
Sign up to set email alerts
|

A loyalty scheme to encourage physical activity in office workers: a cluster RCT

Abstract: Background Increasing physical activity in the workplace can provide physical and mental health benefits for employees and economic benefits for the employer through reduced absenteeism and increased productivity. However, there is limited evidence on effective behaviour change interventions in workplace settings that led to maintained physical activity. This study aimed to address this gap and contribute to the evidence base for effective and cost-effective workplace interventions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 188 publications
(300 reference statements)
0
21
0
Order By: Relevance
“…Participants randomly assigned (in clusters) to the control arm received no intervention during the 6-month intervention period but were placed on a waiting list to participate in the scheme at the end of the study period (ie, 12 months). A more detailed overview of the trial procedures, including the Consolidated Standards of Reporting Trials (CONSORT) flow diagram, and intervention program has been published [4] and is summarized in Multimedia Appendix 1. The Consolidated Standards of Reporting Trials of Electronic and Mobile HEalth Applications and onLine TeleHealth (CONSORT-EHEALTH) checklist has been completed for this study [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants randomly assigned (in clusters) to the control arm received no intervention during the 6-month intervention period but were placed on a waiting list to participate in the scheme at the end of the study period (ie, 12 months). A more detailed overview of the trial procedures, including the Consolidated Standards of Reporting Trials (CONSORT) flow diagram, and intervention program has been published [4] and is summarized in Multimedia Appendix 1. The Consolidated Standards of Reporting Trials of Electronic and Mobile HEalth Applications and onLine TeleHealth (CONSORT-EHEALTH) checklist has been completed for this study [24].…”
Section: Methodsmentioning
confidence: 99%
“…The PAL scheme was a complex physical activity intervention that offered financial incentives and other behavior change techniques delivered via the study website to increase workplace physical activity (recorded by outdoor sensors located within 2 km of the workplace). Paradoxically, results showed that there was a small but significant decline in pedometer steps per day at 6 months relative to the baseline for the intervention group compared with controls, which dissipated at 12 months [4]. Mediation and moderation analyses showed that decreases in physical activity were partially mitigated by positive indirect effects through the constructs of integrated regulation, intrinsic motivation, and habit measured at 6 months, whereas the negative intervention effect was moderated by participants’ perceptions of availability of physical activity opportunities in the workplace environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…The primary outcome was steps/day objectively measured over seven consecutive days using sealed pedometers (Yamax Digiwalker CW-701, Japan) (Bassett et al, 1996;Bravata et al, 2007;Schneider, Crouter, Lukajic, & Bassett, 2003), considered valid if the participant provided ≥250 steps/day for three or more days (Tudor-Locke et al, 2005). These cut-points are in line with those used in the study's main outcomes analyses (Hunter et al, 2019(Hunter et al, , 2018. This outcome was collected at baseline, six and 12 months.…”
Section: Physical Activity Behaviormentioning
confidence: 99%
“…Whilst the study was specifically powered to detect between-group differences in primary outcome (i.e. pedometer steps/day) (Hunter et al, 2019(Hunter et al, , 2018, post-hoc power calculations have been conducted to determine power levels for all mediator analyses using the app developed by Schoemann and colleagues specifically for mediation analyses (Schoemann, Boulton, & Short, 2017). Results are reported in tables 2 and 3.…”
Section: Post-hoc Power Analyses and Sensitivity Analysesmentioning
confidence: 99%
See 1 more Smart Citation